STRUCTURAL DESIGN OF RESIDENTIAL TOWER IN CILINCING FLOOD RESILIENT HOUSING AREA - Eleandro Purnomo, Gerald
ii ABSTRACT STRUCTURAL DESIGN OF RESIDENTIAL TOWER IN CILINCING FLOOD RESILIENT HOUSING AREA Gerald Eleandro Purnomo (15019150) The Cilincing area in North Jakarta is a densely populated area that is vulnerable to flood disasters. Therefore, a three-story amphibious residential building is designed to be earthquake-resistant. Two structures are designed as one unit: a wooden structure as the load-bearing structure for live loads and a concrete structure as the load-bearing structure for earthquake loads. The wooden structure will be supported by the concrete structure through corbel elements. In the placement of the wooden structure, the assumption of zero friction is used, so the wooden structure is assumed not to bear earthquake loads, and the concrete structure bears the entire earthquake load. Analysis is conducted for both types of structures. The loading used in the structural analysis is based on SNI 1727:2020 and SNI 1726:2019. The modeling of both structures is done separately using the ETABS software. The design of the wooden structure includes allowable stress analysis using the ASD (Allowable Stress Design) method and connection design based on SNI 7973:2013. The results of the wooden structure analysis are then applied to the modeling of the concrete structure as additional loads on the corbel elements. Subsequently, the concrete structure is designed, including seismic analysis based on SNI 1726:2019 and the design of beam, column, and corbel elements based on SNI 2847:2019. Based on its seismic design category, a reinforced concrete moment-resisting frame system is used as the earthquake-resistant structural system. There are five types of wooden structural connections designed, including beam-column connections, beam-joist plate connections, gording-rafter connections, rafter-roof beam connections, and column-rafter connections using bolt connectors and steel plates. For the concrete structure, calculations are made for beam reinforcement, column reinforcement, checking the strong column-weak beam (SCWB) criteria, checking column slenderness, corbel reinforcement, and joint shear checks.